Studi Radiografi Makro Dengan Variasi Jarak Sumber Sinar-Bayangan (SID) dan Ukuran Fokus Terhadap Pembesaran Bayangan - Suriansyah, Nanang; Setiawati, Evi; Firdausi, K. Sofjan (BERKALA FISIKA, 2007)
The dependence of radiograph magnification (M) on the ratio focal spot size to object ( has been studied. The object shape like a coin made from iron which different diameter and variation focal spot size have been used. The experiment condition were set up at the distance of the object to the film of 0 cm (object stick the film) and 45 cm, with the tube voltage of 50 kV, tube’s current of 100 mA, and time of 0.04 s. The results show that the increasing of (leads to the increasing of (M) when the distance of the object to the film is more than 0 (b>0). Keyword: focal spot, SID, magnification radiograph